1996
DOI: 10.1016/s0165-1161(96)90182-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of peak exposure to genotoxic carcinogens

Abstract: Relevance of the key question 18 Theoretical values of the DRCF 21 Instantaneous high-dose versus long-term low-dose exposures 21 Short-term low-dose versus long-term low-dose exposures 23 Cessation of exposure 24 Conclusion 25 Experiments with genotoxic carcinogens 26 Single-dose versus multiple-dose exposure regimens-tumour development 26 Multiple-dose versus extended multiple-dose exposure regimenstumour development 31 Experiments with genotoxic carcinogensparameters other than tumour development 33 4 4.1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This is because it is by no means certain that increasing the exposure duration (e.g., with a factor of 2) has the same impact on cancer risk as increasing the exposure level with the same factor. In fact, examples are available that this is not (always) the case (Verhagen et al, 1994;Voorrips et al, 2000). Unfortunately, occupational epidemiological studies are almost never analyzed with exposure level and duration as separate terms in the model.…”
Section: Exposure Metrics In Epidemiological Analysesmentioning
confidence: 99%
“…This is because it is by no means certain that increasing the exposure duration (e.g., with a factor of 2) has the same impact on cancer risk as increasing the exposure level with the same factor. In fact, examples are available that this is not (always) the case (Verhagen et al, 1994;Voorrips et al, 2000). Unfortunately, occupational epidemiological studies are almost never analyzed with exposure level and duration as separate terms in the model.…”
Section: Exposure Metrics In Epidemiological Analysesmentioning
confidence: 99%
“…Although the relevance of carcinogenicity as an endpoint for acute exposure is a controversial issue, and the actual risk of cancer may be low even in the case of potent genotoxic carcinogens, the possibility of acute exposure related carcinogenicity cannot be excluded (Bos et al, 2004;Christou, 2000). Current data are limited, but some animal studies provide evidence of cancer processes induced by single exposures to potent genotoxic carcinogens (Verhagen et al, 1994). Moreover, the release of carcinogenic substances causes a great deal of concern among the general public.…”
Section: Resultsmentioning
confidence: 99%
“…However, doserate (and thus time) may also be an important determinant for tumor induction. Based on an evaluation of the available literature, Verhagen et al (1994) concluded that a carcinogenic dose administered in a relatively short period of time showed a higher carcinogenic potency than when the same total dose was divided over a longer period of time and the use of a dose-rate correction factor was proposed. Felter et al (2011) proposed a framework for assessing health risks from lessthan-lifetime exposures to carcinogens.…”
Section: Dose Metrics In Inhalation Exposuresmentioning
confidence: 99%